Penurunan Penyusutan Serpihan Emas di Departemen Hollow PT. Untung Bersama Sejahtera - Anthony Wasisto (Jurnal Titra, 2016)
PT Untung Bersama Sejahtera (UBS) is a gold jewelry manufacturing company. PT. UBS is facing mass shrinkage problems which is about 3.16% during the manufacturing process. Most of the shrinkage occurs in the Hollow Division at PAK and PAF. The purpose of this study is to reduce the shrinkage which occurs in the Division Hollow by using DMAIC method. Based on direct observation in PAK and PAF there are several problems which cause shrinkage: container vessel gold flakes that do not fit the size of the milling machine, there is no cover on the front of the milling machine, the gold flakes fall to the floor, and the gold flakes that stick to the sandals. Improvement on the PAK and PAF are done by machine modifications, floor space repair, and control the actions that have been made. Shrinkage can be reduced up to 1.28% when improvement applied in UBS.